2013
DOI: 10.1096/fj.12-225664
|View full text |Cite
|
Sign up to set email alerts
|

Signal transducer and activator of transcription‐3 (Stat3) plays a critical role in implantationviaprogesterone receptor in uterus

Abstract: Recent studies have shown that activation of the signal transducer and activator of transcription-3 (Stat3) is required for decidualization, interacting with progesterone receptor (PR) in uterus. Based on previous reports, we hypothesized that crosstalk between STAT3 and PR signaling is required for successful implantation. To identify the interaction between STAT3 and PR isoforms, we performed immunoprecipitation following transient cotransfection and found that STAT3 physically interacted with PR-A, which is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
90
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(91 citation statements)
references
References 42 publications
1
90
0
Order By: Relevance
“…Although there is no special indications that whether the polyploidization of stromal cells is existed, uterine Stat3 knockout are defective in hormonally induced decidual reaction, clearly with the absence of stromal cell polyploidization. 40 In summary, our results illustrate that E2F8 expression in stromal cells is regulated by progesterone through activating HB-EGF/EGFR/ERK/STAT3 signal pathway.…”
Section: Progesterone Activates the Expression Of E2f8 Through Hb-egfmentioning
confidence: 52%
See 1 more Smart Citation
“…Although there is no special indications that whether the polyploidization of stromal cells is existed, uterine Stat3 knockout are defective in hormonally induced decidual reaction, clearly with the absence of stromal cell polyploidization. 40 In summary, our results illustrate that E2F8 expression in stromal cells is regulated by progesterone through activating HB-EGF/EGFR/ERK/STAT3 signal pathway.…”
Section: Progesterone Activates the Expression Of E2f8 Through Hb-egfmentioning
confidence: 52%
“…STAT3 had been tightly linked to implantation and decidualization in mice and humans. 40,41 Conditional ablation of Stat3 in mouse uterus results in embryo implantation failure. Although there is no special indications that whether the polyploidization of stromal cells is existed, uterine Stat3 knockout are defective in hormonally induced decidual reaction, clearly with the absence of stromal cell polyploidization.…”
Section: Progesterone Activates the Expression Of E2f8 Through Hb-egfmentioning
confidence: 99%
“…LIF is an essential mediator of estrogen and can replace nidatory estrogen in the activation of delayed implantation (4). LIF activates the phosphorylation of transcription factor STAT3, which is also indispensable for implantation (12). As a previous study has shown two potential STAT3 binding sites in Egr1 promoter (31), we hypothesized that estrogen might control the expression of Egr1 through LIF-STAT3 pathway.…”
Section: The Regulation Of Estrogen On Lif-stat3mentioning
confidence: 94%
“…The stromal localization of LIF is similar to phosphorylated STAT3 expression pattern (10). Conditional knock-out or transient suppression of STAT3 results in implantation failure, which suggests the critical role of STAT3 during implantation (11)(12)(13)(14). As a pleiotropic cytokine, LIF is also essential for mouse and human decidualization (15,16).…”
mentioning
confidence: 84%
“…This signaling pathway, including Stat3 nuclear translocation in the luminal and glandular epithelium, is attenuated in LIF null mutant uteri (Cheng et al, 2001). Recent studies further demonstrate that uterine conditional deletion of Stat3 also induces implantation failure (Lee et al, 2013, Pawar et al, 2013, Sun et al, 2013. In the human, a low level of LIF is associated with unexplained recurrent abortion and infertility (Hambartsoumian, 1998, Piccinni et al, 1998.…”
Section: Cytokinesmentioning
confidence: 99%